Pendidikan Inklusif pada Anak Berkebutuhan Khusus - Adibussholeh HM; Siti Wahyuni (Indonesian Journal of Humanities and Social Sciences, 2021)
The education process of children with special education is not like implementing education in "normal" children. They must get treatment with special skills for teachers and stakeholders involved in the implementation of education. This study uses a qualitative approach. This study showed that the curriculum model applied is adjusted to the initial assessment and learning development results, including duplication, modification, substitution, and most models.